LPN-Based Model Repair Method for Changed Business Processes - Du, Yuyue; Xu, Yuhua; Qi, Liang; Liu, Yijia; Wang, Qun; Chen, Mei (Computing and Informatics, 2026)
<span data-slate-fragment="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">Information systems play an important role in realizing business processes. Process mining uses event logs produced by information systems to construct the models of business processes. Then, the business process model can be used to verify and improve business processes. To represent a changing business process, some structures of the process model need to be replaced with other structures. However, existing model repair methods do not consider replacing the structures of the process model. This work proposes a logical Petri net-based approach to repair models based on the order relations among activities. First, we construct two relation sets of an event log and a process model, respectively. Comparing the two relation sets, the differences between a process model and an event log are collected in a deviation set. According to the deviation set, the model is repaired by constructing concurrent structures. Finally, we perform some experiments to illustrate the effectiveness and correctness of the proposed approach. The results show that the proposed method produces a more precise and simpler repaired model compared to state-of-the-art methods.